INNOVATION AND ISLAMIC FINANCIAL FATWA IMPROVING AGRICULTURAL PRODUCTIVITY - Umrotul Khasanah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The Islamic financial system and its innovations can stimulate agricultural productivity and provide welfare for farmers. This study aims to: (1) reveal the views of farmers about innovation and the fatwa of ulama, (2) farmers' opinions on the Islamic financial system, and (3) farmers' statements about the traditional Islamic financial system in increasing productivity. The research uses a descriptive qualitative case study method with a Giddens structuration approach. This research is concerned with meaning, context, and emic perspective. Data analysis by analyzing important statements, formulating, describing, and reducing data to findings, propositions, and conclusions. Data collection and analysis were carried out simultaneously, prioritizing observation and interviews and the researcher himself as the main instrument. The research findings show the importance of innovation in Islamic finance. Farmers feel very helped by traditional Islamic financial systems such as partnership, one-third share, and one-half share models. The system can help farmers, both the landowner and land manager. The existence of the traditional Islamic financial system supports the welfare of the farming. Better if Indonesia Islamic financial institutions adopt the system. So that financing for farmers becomes easier and encourages the progress of the agricultural sector in Indonesia.